Heat Transfer Characteristics of Passive, Active, and Hybrid Impinging Jets: A Review - Michel Matar; Mohammad El Hassan; Nikolay Bukharin; Anas Sakout; Ali Hammoud; Hassan H. Assoum (International Journal of Technology)
In engineering applications, there is a need to reform the excitation techniques used for jet impingement to achieve simpler, more effective thermal exchange. Jet impingement is a highly effective method for enhancing heat transfer due to its ability to create high heat transfer coefficients. This makes it a preferred technique in applications requiring efficient thermal management, such as cooling of electronic components, turbine blade cooling in jet engines, and material processing. However, traditional excitation techniques for jet impingement can be complex and challenging to implement. Therefore, there is a growing interest in developing new excitation methods that are simpler and more effective. The employed techniques can be categorized into three groups: passive self-excited jets, active excited jets, and hybrid techniques. Passive methods, such as annular, swirling, and sweeping jets, utilize the inherent characteristics of the jet flow without requiring additional energy consumption. Active systems, on the other hand, involve supplementary devices like fans or pumps to intensify heat transfer. Examples of active excited jets include synthetic and pulsed jets. Hybrid techniques combine two or more methods to further thermal improvement. This paper reviews experimental and numerical hybrid techniques to enhance heat transfer to impinged surfaces. Experimental tools, including high-speed imaging, Particle Image Velocimetry (PIV), and infrared thermography, are shown. Numerical simulation methods, such as Computational Fluid Dynamics (CFD), are reviewed. The efficacy of these methods is evaluated by comparing their performance, highlighting potential for optimization and innovation in jet impingement heat transfer.